Tecnologias educacionais para o atendimento de estudantes com transtorno do espectro autista em tempos de pandemia na educação profissional e tecnológica - Nunes, Marcela Martins (2023)
The present work is part of the line of research Innovation for Professional and Technological Education of the academic master's degree in Professional and Technological Education of the Colégio Técnico Industrial de Santa Maria. The research was developed from the following question: What educational technologies are used to care for students on the autistic spectrum in times of a pandemic at EPT? Based on this question, we sought to identify which digital technologies and tools are offered to students of technical courses of the Federal Network of Professional, Scientific and Technological Education, their contributions to minimizing the consequences of social distancing and efficiency in teaching and learning processes, enabling the inclusion of autistic students. The research methodology is based on a qualitative approach with a case study, the research subjects were the teachers working at EPT who have students diagnosed within the Autistic Spectrum Disorder (ASD). The data collection instrument used was a questionnaire with survey-type questions with open and closed questions, sent by email to 1563 professors from institutions linked to the EPT modality. We obtained 61 answers and the data were analyzed and the results were discussed. From which it was inferred that the pandemic highlighted both the benefits and challenges of using educational technologies. In this regard, it is important that educators continue to explore the potential of these technologies, while working to overcome the challenges and ensure that all students have equal access to a quality education